Stick & Scones - Davidson, Diane Mott (Bantam Books, 2001)
Colorado cataerer Goldy Schulz is excited about the chance to cook real Elizabethan food at Hyde Castle. Her first day on the job is ruined by finding a dead body in Cottonwood Creek and having someone shoot at her, twice.